Genomic discovery and structural dissection of a novel type of polymorphic toxin system in gram-positive bacteria - Huan Li; Yongjun Tan; Dapeng Zhang (Computational and Structural Biotechnology Journal, 2022)
Bacteria have developed several molecular conflict systems to facilitate kin recognition and non-kin competition to gain advantages in the acquisition of growth niches and of limited resources. One such example is a large class of so-called polymorphic toxin systems (PTSs), which comprise a variety of the toxin proteins secreted via T2SS, T5SS, T6SS, T7SS and many others. These systems are highly divergent in terms of sequence/structure, domain architecture, toxin-immunity association, and organization of the toxin loci, which makes it difficult to identify and characterize novel systems using traditional experimental and bioinformatic strategies. In recent years, we have been developing and utilizing unique genome-mining strategies and pipelines, based on the organizational principles of both domain architectures and genomic loci of PTSs, for an effective and comprehensive discovery of novel PTSs, dissection of their components, and prediction of their structures and functions. In this study, we present our systematic discovery of a new type of PTS (S8-PTS) in several gram-positive bacteria. We show that the S8-PTS contains three components: a peptidase of the S8 family (subtilases), a polymorphic toxin, and an immunity protein. We delineated the typical organization of these polymorphic toxins, in which a N-terminal signal peptide is followed by a potential receptor binding domain, BetaH, and one of 16 toxin domains. We classified each toxin domain by the distinct superfamily to which it belongs, identifying nine BECR ribonucleases, one Restriction Endonuclease, one HNH nuclease, two novel toxin domains homologous to the VOC enzymes, one toxin domain with the Frataxin-like fold, and several other unique toxin families such as Ntox33 and HicA. Accordingly, we identified 20 immunity families and classified them into different classes of folds. Further, we show that the S8-PTS-associated peptidases are analogous to many other processing peptidases found in T5SS, T7SS, T9SS, and many proprotein-processing peptidases, indicating that they function to release the toxin domains during secretion. The S8-PTSs are mostly found in animal and plant-associated bacteria, including many pathogens. We propose S8-PTSs will facilitate the competition of these bacteria with other microbes or contribute to the pathogen-host interactions.